An attempt to develop a detection method specific for virulent duck plague virus strains based on the UL2 gene B fragment. Issue 6 (2nd November 2017) - Xie, Liji; Huang, Li; Xie, Zhixun; Wang, Sheng; Huang, Jiaoling; Zhang, Yanfang; Zhong, Chuande
ABSTRACT: A comparison of the unique long region 2 (UL2) gene sequences between 10 virulent and 11 attenuated duck plague virus (DPV) strains (including all DPV UL2 gene sequences registered in GenBank) showed that the UL2 genes in the attenuated DPV strains had a 528 bp deletion in the B fragment. Primers were designed based on the B fragment sequence of the UL2 gene in an attempt to establish a fluorescence quantitative polymerase chain reaction (PCR) and a conventional PCR detection method that could specifically detect virulent DPV strains (i.e. positive detection for virulent DPV strains and negative detection for attenuated DPV strains). Additionally, PCR products were cloned for sequence analysis. These two methods detected five attenuated DPV strains in addition to the virulent DPV strains. Sequence analysis of the PCR products showed that the amplified products were the B fragments of the UL2 gene. These results indicated that detection methods specific for virulent DPV strains could not be established using primers designed based on the UL2 gene B fragment.